Application of PBL Model Assisting The Chemo-Edutainment Based Worksheets for Increasing The Students’ Activities and Critical Thinking (Journal of Innovative Science Education, 2018)
This study aim to determine the effect application model PBL-assisted worksheet chemo-edutainment to critical thinking and student’s activity. Population in this study is class XI-IPA student SMA 1 Karanganyar, Demak school year 2016/2017. Determination of the sample with cluster random sampling system obtained two classes to be sampled is a class XI-IPA2 as a class of experiments that are treated using PBL-assisted worksheet chemo-edutainment and XI-IPA4 as a control group who received treatment using conventional method-assisted worksheet from the other. The research data obtained by the method of tests, questionnaires, observation. The results of the study, obtained results of the experimental group had an average of 73,19 and a control group had an average of 65,06. Based on the analysis, obtained by the experimental group is better than the control group is shown with tcount (4,417) > Ttable (1.99) for the critical thinking and than tcount (4.687) > Ttable (1.99) for student’s activity in a classroom . The conclusions of this research is the application of model PBL-assisted worksheet chemo-edutainment to critical thinking and student’s activity on meteri solubility and solubility product, with the level of unfluence on critical thinking outcomes are 45,55% and the amount of influence on the activity of students is 60,44%.